Simulation and optimization of steam generation in a pulp and paper mill - Ji, Xiaoyan; Lundgren, Joakim; Wang, Chuan; Grip, Carl-Erik (Luleå tekniska universitet, Energivetenskap, 2011)
A mathematical process integration model for the steam generation part (recovery boiler, bark boiler, and turbine) was developed based on a pulp and paper mill in the Northern Sweden. The material and energy balances were calculated theoretically and then the operation data from a pulp and paper mill in the Northern Sweden were used to validate the simulation results. By implementing it into the whole plant, the effect of the operation conditions on the whole plant performance were investigated. The introductory studies were carried out with an objective function to minimize the energy cost. The influence of different parameters was rigorously studied. The correlation between economic and energy optima was discussed. Godkänd; 2011; 20111024 (ysko)